Analisis Pembelajaran Al-Qur’an Hadits di Man 2 Karawang: Studi tentang Metode, Fasilitas, dan Faktor Pendukung Penghambat - Amelda Febriani, Tia; Kautsar Azhar, Tazkia; Nova Saputri, Ajeng; Emilia Putri, Vini; Khaerani Hasibuan, Tiara (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This research was conducted at MAN 2 Karawang, focusing on the analysis of Al-Qur'an and Hadith learning, particularly regarding methods, facilities, as well as supporting and inhibiting factors. The location was chosen based on the school's commitment to developing flagship programs such as the Tahfidz Al-Qur'an (Qur'an memorization) and Rohis (Islamic Spiritual) mentoring, alongside the challenges faced in optimizing the memorization of Juz 30 and students' understanding of Arabic script. The research method used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that innovative methods such as Market Place Activity, Snowball Throwing, and Role Play proved effective in increasing student participation and comprehension. Facilities such as a large TV for Tahsin (Qur'an recitation improvement) and a Rohis room also served as key supporting factors. However, obstacles such as extreme weather and power outages occasionally disrupted the learning process. In conclusion, a combination of creative methods, adequate facilities, and teacher adaptability played a crucial role in the success of Al-Qur'an and Hadith learning at MAN 2 Karawang, although infrastructure improvements are needed to address technical challenges.